IDDF2019-ABS-0116 Self-completion method of endoscopic submucosal dissection using a novel endo-knife: an ex vivo pig model study. (June 2019) - Esaki, Mitsuru; Horii, Toshiki; Ichijima, Ryoji; Suzuki, Sho; Kusano, Chika; Ikehara, Hisatomo; Gotoda, Takuji
Abstract : Background: Endoscopic submucosal dissection (ESD) is a standard treatment for gastrointestinal tract tumors. Various endoscopic devices have been developed to improve the ESD procedure. We invented a self-completion ESD method using an Endosaber, which is a novel needle-type endo-knife for ESD (figure 1 ). Only one Endosaber was used without any additional device. In addition, ESD could be performed only by one operator without any assistance during the procedure. The aim of the study was to evaluate the technical outcomes of this method in an ex vivo pig training model. Methods: This was a pilot study. ESD procedures were performed by four experts. Mock lesions of 15 mm diameter were made in the middle or lower esophagus of the porcine models. Each operator performed three ESDs on the mock lesions. The primary outcome was the completion rate of the self-completion ESD method. The secondary outcomes were the procedure time, en-bloc resection rate, perforation rate, and number of injections during the procedure. Results: In this study, all 12 cases of ESD were completed using the self-completion method (completion rate: 100%). The median procedure time (range) was 483.5 (276–936) seconds [median incision time; 240.4 (98–605) seconds and median dissection time; 222 (137–617) seconds]. En-bloc and complete resection rates were 100% each. No perforation was noted during any of the procedures. The median number of injections was 10.5 (4–15). The procedure time significantly decreased with experience (P = 0.0199). Conclusions: The self-completion ESD method using only one Endosaber without any assistance achieved a 100% en-bloc resection rate without any perforation. Reduction in the need for an additional device or assistance was successful. This method may contribute to reducing the total cost of ESD procedure.